Penegakan Hak-Hak Ekologis Masyarakat Setempat Sebagai Wujud Pengakuan Eksistensi Manusia Menurut Armada Riyanto - Severinus Savio Cimi; Edison R.L. Tinambunan (Jayapangus Press, 2023)
This research is motivated by the phenomenon of environmental damage that hurts people's lives. The increasingly massive use of nature causes environmental damage that has the potential to disrupt the lives of local people. There are many practices of extracting Natural Resources without taking into account the plight of the local population. People's lives are disrupted so that the right to live in a safe environment is not fully enjoyed. Ecological rights that are naturally embedded in the community then do not find their fulfillment. Against this fact, the study of ecological rights based on Fleet Riyanto's thoughts will be described in this research. The results of this study reveal that local people are subjects who are commensurate, equal, and dignified with everyone. This study uses a literature study method by tracing the scientific literature and digging up facts from newspapers. Relational philosophy of Armada Riyanto will present a perspective that focuses on people or communities whose rights are being ignored. The fruits of his thoughts will at the same time become a scalpel to resolve the ecological rights issues that occur. The goal to be achieved is to find the true existence of the community whose ecological rights are being ignored. The fullness of its existence occurs when its ecological rights are well guaranteed as experienced by other people in general. They are human beings who naturally want their ecological rights to be fulfilled.